A 10-year review of isoniazid-resistant TB management in Uzbekistan 2009-2020 - M.L. Rekart; P. Thit; M. Oluya; S. Moe; T. Hasan; N. Parpieva; K. Safaev; A. Khristusev; T. Zinaida; J. Singh; S. Allamuratova; I. Azamat; et al. (IJTLD Open)
BACKGROUND: Isoniazid (INH, H) resistance is the most common drug-resistant TB pattern, with treatment success rates lower than those in drug-susceptible TB. The WHO recommends a 6-month regimen of rifampicin (RIF, R), ethambutol (EMB, E), pyrazinamide (PZA, Z), and levofloxacin (Lfx) (6REZLfx) for INH-resistant, RIF-susceptible TB (HRRS-TB). Uzbekistan has a high burden of TB (62/100,000 population) and multidrug-resistant TB (12/100,000 population). METHODS: We conducted a retrospective, descriptive study of microbiologically confirmed HRRS-TB using routinely collected programmatic data from 2009 to 2020. RESULTS: We included 854 HRRS-TB cases. Treatment success was 80.2% overall. For REZLfx, the treatment success rate was 92.0% over a short treatment duration, with no amplifications to RIF or second-line anti-TB drug resistance. We documented 46 regimens with REZLfx plus linezolid (success 87.0%) and 539 regimens using kanamycin or capreomycin (success 76.6%). We identified 37 treatment failures (4.3%), 30 deaths (3.5%), 25 resistance amplifications (2.9%), including eight to RIF (0.9%), and 99 lost to follow-up (LTFU) cases (11.6%). Unsuccessful outcomes were more common with older age, diabetes, chest X-ray cavities, smear positivity, smear-positive persistence, and male sex. LTFU was more common with injection-containing regimens. CONCLUSIONS: REZLfx is a safe and effective first-line treatment for INH-resistant, RIF-susceptible TB. Treatment success was lower and LTFU was higher for injection-containing regimens.